Ambient energy harvesting from colored multiplicative noise. (December 2022) - Mondal, Shrabani; Koley, Santanu
Abstract: The present study examines the effect of multiplicative Gaussian noise on the conversion of vibration energy into electrical energy. Nonlinear oscillators are considered in the present model. The results demonstrate that similar to additive noise case, the harvesting of the vibration energy to electricity could be good if the voltage can closely track the advancement of the amplitude of the oscillator. Another observation is that the power of the micro-electromechanical systems (MEMS) goes through a maximum as with inverse of noise correlation time. Further, the position of the maxima in power generation occurs for higher noise correlation time due to the space dependency associated with the multiplicative Gaussian noise. Along with these, we have investigated how the power generation is dependent on the environment, properties of the oscillating systems and the piezoelectric dynamics.